Anisotropic and Tunable Vocal Fold Phantom for Biomechanical Modeling - Sarrafzadeh, Afarin; Erdil, Kuter; Tavli, Onur; Ferhanoglu, Onur; Erten, Ahmet C. (Ieee, 2025)
Modeling the human vocal folds using an accurate vocal fold replica with exact characteristics such as anisotropic behavior and tunable mechanical properties remains challenging. In this study, we have introduced an effective and simplified approach to overcome vocal fold modeling challenges and achieve more realistic samples by using a silicon-based cubic phantom with a natural latex rubber tube embedded in the center of the cube. Young's modulus tunability in the longitudinal direction was achieved with a variation in water-to-air ratio inside the tube within the physiological range of 2 to 40 kPa while maintaining a constant Young's modulus in the transverse direction. Finite element simulations based on COMSOL in addition to experimental testing verified the effectiveness of the method indicating that reaching higher stiffness in the longitudinal direction by increasing the amount of water preserved anisotropic behavior. In summary, the main contribution of this study is introduction of an alternative approach to modelling the vocal fold with precise Young's modulus values within a single sample by adjusting the water ratio, which increases precision in experiments and reduces fabrication times.
21st International Conference on Synthesis, Modeling, Analysis and Simulation Methods and Applications to Circuit Design-SMACD -- JUL 07-10, 2025 -- Istanbul, TURKIYE
Keywords: Vocal Fold Phantom; Anisotropy; Tunable; Fluid Inclusion; Young'S Modulus